Effectiveness of “tumor necrosis factor inhibitors” in monogenic hereditary recurrent fevers in children and adolescents: a systematic review - Dhahri, Rim; Boussaid, Soumaya; Ammar, Lobna Ben; Fenniche, Insaf; Ben Ayed, Hiba; Rahmouni, Safa; Zouaoui, Khaoula; Rekik, Sonia; Amri, Khalil; Sahli, Hela; Gharsallah, Imène (Frontiers in Immunology, 2025)
IntroductionThis systematic review aims to evaluate the clinical effectiveness of tumor necrosis factor (TNF) inhibitors in treating monogenic hereditary recurrent fevers (HRFs) in children and adolescents.MethodsWe conducted a comprehensive literature search across MEDLINE, EMBASE, and Scopus up to May 2024, including case reports, case series, and observational studies involving pediatric patients with HRFs treated with TNF inhibitors. Articles were screened and selected based on PRISMA guidelines.ResultsEleven pediatric cases were identified from ten studies, including patients with FMF (n=2), MKD/MKD (n=5), TRAPS (n=2), and CAPS (n=2). Etanercept was the most frequently used TNF inhibitor (10/11 cases), and infliximab was used in one FMF case. Follow-up duration ranged from 3 months to 4 years. Clinical responses varied: full remission in TRAPS cases; partial improvement in some MKD and CAPS cases; and no significant effect in several FMF and MKD/MKD patients. Etanercept showed the best outcomes in TRAPS, while responses in CAPS and MKD/MKD were inconsistent.Clinical trial registrationTNFi may offer a therapeutic option for selected pediatric HRF cases, particularly colchicine-resistant FMF with articular symptoms or where IL-1 blockers are unavailable. However, their efficacy appears limited and variable across HRF subtypes. Larger studies are needed to better define the role of TNF inhibitors in pediatric HRFs.